Understanding discrepancy in autism epidemiology in view of underpinning genetic architecture: Lessons learnt from studies in consanguineous populations. (May 2022) - Idris, Ahmed B.; Al-Mamari, Watfa; Abdulrahim, Reem; Alsayegh, Abeer
Abstract: This short commentary aims to shed light on the discrepancy in the epidemiological findings and underlying genetic architecture of Autism Spectrum Disorder (ASD) between demographically distinct populations; consanguineous and non-consanguineous. Here we discuss the effect of advanced paternal age as a risk factor acting as a proxy for potential underlying genetic mechanisms. On that account, this narrative postulates that disparity might possibly be explained in the context of the differences in genetic makeup and abundance of recessive mutations in the highly consanguineous populations.